Observation of the B0s → J/[psi]K0SK+-π-+ decay - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2014)
Decays of the form B(s)0 → J/ψKS0h+h(′) −(h(′) = K, π) are searched for in proton-proton collision data corresponding to an integrated luminosity of 1.0 fb−1 recorded with the LHCb detector. The first observation of the Bs0 → J/ψKS0K±π∓ decay is reported, with significance in excess of 10 standard deviations. The B0 → J/ψKS0K+K− decay is also observed for the first time. The branching fraction of B0 → J/ψKS0π+π− is determined, to significantly better precision than previous measurements, using B0 → J/ψKS0as a normalisation channel. Branching fractions and upper limits of the other B(s)0 → J/ψKS0h+h(′) − modes are determined relative to that of the B0 → J/ψKS0π+π− decay.